Kandungan nutrisi dan fraksi serat sorgum samurai varietas II sebagai bahan baku pakan ruminansia pada berbagai usia panen dan dosis pemupukan - Anwar Efendi Harahap; Arsyadi Ali; Triani Adelina; Evi Irawati; Irwan Taslapratama; Fitri Harianti (Fakultas Pertanian Universitas Majalengka, 2026)
The purpose of this study was to examine the nutritional value and fiber fraction of the Samurai sorghum variety II due to the harvest age and urea fertilizer dosage levels in producing high-nutrient forage raw materials. This study used a completely randomized plan factorial pattern (3 x 3) with 3 replications. The first factor was the treatment of harvest age of 60, 65 and 70 days, and the second factor was the urea fertilizer dosage of 150, 200, and 250 kg ha-1. The parameters observed included crude protein (%), crude fiber (%), crude fat (%) and NDF (%), ADF (%), and hemicellulose (%) in the Samurai sorghum variety II. The data obtained was analyzed with General Linear Models (GLM) and further tested with the Tukey Test. The results showed that there was no interaction between cutting age and urea fertilizer dose on the content of crude protein (%), crude fiber (%), crude fat (%), NDF, ADF, and hemicellulose in the Samurai sorghum variety II. There are also no significan differences caused by each factor, except for the variable of the average value of crude fiber at the 70-day cutting age which is higher compared to other cutting ages. The conclusion that there was no effect of interaction between harvest age and fertilizer dose on crude protein (%), crude fiber (%), crude fat (%) and NDF (%), ADF (%), and hemicellulose (%). The conclusion of this study is that the best treatment, namely the best treatment, is the single factor of 65 days of cutting age because it is able to reduce crude fiber.